2018
DOI: 10.7819/rbgn.v20i1.3684
|View full text |Cite
|
Sign up to set email alerts
|

Consumers in a social network: the perception of clothing quality per gender

Abstract: Purpose -The general objective of this paper is to evaluate the determinant attributes of the perception of clothing quality by the users of a social network and to verify if there are any differences of evaluation of these determinants between genders.Design/methodology/approach -To achieve the objective, a survey was conducted with a sample of 295 consumers. All participants, regardless of gender, were asked to access the SurveyMonkey site link and to answer the questions regarding the quality of clothing fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…First and foremost, sex has not resulted in being a decisive socio-demographic variable in the assessment of perceived garment quality. This is a clear discrepancy with the existing research (Gitimu et al, 2013, Freire Castelo & de Oliveira Cabral, 2018, Lee & Workman, 2021. One can object that this is because our volunteer sample (120 respondents) was much smaller than the convenience sample (246 respondents).…”
Section: Discussionmentioning
confidence: 58%
“…First and foremost, sex has not resulted in being a decisive socio-demographic variable in the assessment of perceived garment quality. This is a clear discrepancy with the existing research (Gitimu et al, 2013, Freire Castelo & de Oliveira Cabral, 2018, Lee & Workman, 2021. One can object that this is because our volunteer sample (120 respondents) was much smaller than the convenience sample (246 respondents).…”
Section: Discussionmentioning
confidence: 58%
“…The identification process of consumer preferences toward apparel products can also be conducted through intrinsic (Wilfling et al, 2021). Additionally, previous studies found that in product cues investigation, intrinsic cues of apparel products affect consumer brand preferences (Bezuidenhout et al, 2016;Castelo & Cabral, 2018;Fiore & Damhorst, 1992;Shukla et al, 2022). Along with extrinsic cues, intrinsic cues have an important role in product evaluation to shape consumer brand preferences (Semaan et al, 2019).…”
Section: Intrinsic Cuesmentioning
confidence: 99%
“…The apparel industry faces challenges in satisfying consumers’ needs due to the change of priorities in the previous decades. During the 1980s and 1990s, consumers tended to buy fashionable clothing, whereas today, consumers are generally more value-orientated (Freire Castelo and de Oliveira Cabral, 2018). Understanding consumers’ perceptions of apparel’s quality are essential for providing satisfaction, which could lead to a potential competitive advantage, larger market share and higher revenue for apparel companies.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, one clothing aspect that has to be studied and quantified is comfort. Human perception of clothing comfort is made when sensory information is received, processed and then compared to past sensory experiences, ultimately representing people’s expectations (Rahman, 2011; Freire Castelo and de Oliveira Cabral, 2018). These perceptions lead to the formulation of different clothing attributes, which have different importance for the consumers and affect purchase decisions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation